Conditional Value at Risk (CoVAR) - Hong, KiHoon Jimmy (Henry Stewart Talks, 2010)
Value at Risk failure, Systemic Risk, Need of Conditional Value at Risk, Properties, Endogeneity of Systemic Risk, Tail Dependence Measure, Estimation Method: Quantile Regression, Contribution to Systemic Risk, VaR vs CoVaR, Capital Requirement Implication, Costs of CoVaR, Advantages of CoVaR
Archived at 2022/04/04